Identification Of Noise Sources On Longwall Panels Using Multiple Time-Synchronized Dosimeters (29ca0bb5-2d84-41df-acdc-84917631e72e) - E. Spencer; D. Babich; L. Alcorn; A. Smith (Society for Mining, Metallurgy & Exploration, 2007)
Noise is one of the most pervasive health hazards in mining. A compilation of Mine Safety and Health Administration (MSHA) noise survey data for Fiscal year 1990 shows that approximately 40% of the total samples taken for longwall occupations exceeded the Permissible Exposure Limit (PEL) of 100% [Gigliotti et al. 1991]. In order to properly determine workers’ exposures on longwall coal mining systems, it is necessary to provide accurate baseline measurements for these mining systems. This research was designed to develop guidelines and test procedures for identifying all noise sources that are major contributors to the underground noise exposure of longwall coal mining system workers. Once the high noise sources are identified, promising engineering controls can be tested and evaluated to reduce the noise of the sources. The measurement system used to analyze the noise sources included stationary dosimeters in a documented repeatable pattern and a time-motion study of the cutting cycle and operator’s work cycle. Significant results from the underground measurements show that the highest sound levels recorded are at the stageloader discharge segment and tailpiece controls and remained at about the same level throughout the test.